Pengaruh pemberian minum jahe merah terhadap penurunan intensitas nyeri luka perineum pada ibu nifas di BPM Permata Bunda Tuban - Mariyatul Qiftiyah; Umu Qonitun (Universitas Muhammadiyah Semarang, 2021)
One of the complications experienced by postpartum mothers is the presence of perineal wounds which can cause more severe pain effects (Sumiaty, 2017). One of the non-pharmacological ways to reduce pain is to drink red ginger. The purpose of this study was to determine the effect of drinking red ginger on reducing the intensity of perineal wound pain in postpartum women at BPM Permata Bunda Tuban. This research method is analytic experimental with a pre-experimental design (Static-group comparison design). The sample of this study was 44 postpartum mothers which were divided into 2 groups, namely the control and treatment groups, with a systematic random sampling technique. Data analysis used Sample t-Test (Independent sample t-Test). Based on the results of the study, it was obtained from 22 respondents (postpartum mothers) on the 5th day who were not given drinking red ginger, most of the respondents experienced moderate perineal wound pain as many as 13 (59.10%), while from 22 respondents (postpartum mothers) on the 5th day, most of those who were given red ginger had mild perineal wound pain as much as 12 (54.60%). The results of the analysis using the sample t-test test found that P of 0.000 is smaller than 0.05, then H1 was accepted that there was an effect of giving red ginger to decrease the intensity of perineal wound pain in postpartum mothers at BPM Permata Bunda Tuban